Health Literacy in a Social Context: Review of Quantitative Evidence - Tetine Sentell; Ruth Pitt; Opal Vanessa Buchthal (SLACK Incorporated, 2017)
Background: Conceptual literature has consistently noted that health literacy exists within a social context. This review examined how the intersection of social context and health literacy has been operationalized in quantitative, empirical research. Methods: Following PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, we searched seven databases, including PubMed and CINAHL (The Cumulative Index to Nursing and Allied Health Literature), using a range of potentially relevant keywords, and we hand-searched bibliographies. Inclusion criteria were quantitative studies of any design in which measurement of health literacy and measurement of social context intersected. We identified 1,052 unduplicated articles; 34 met inclusion criteria. Key Results: We found three distinct perspectives on the intersection between health literacy and social context. Most common (n = 23) were studies measuring an association between individual health literacy and individual social capital, social support, or social engagement, particularly whether social support varied by health literacy and/or if this relationship mediated health outcomes. Another group of studies (n = 6) took the perspective that being health literate by definition included social context, including access to and/or use of social support as a domain in individual health literacy assessment. Five studies considered the social context of health literacy as an independent property measured beyond the individual level; two measured community-level health literacy and three measured health literacy capacity/concordance in caregiving dyads. The studies showed significant definitional and measurement complexity and overlap. In the most dramatic example, a similar question was used across various studies to measure (1) health literacy, (2) a social support domain in health literacy, (3) social support, and (4) a study outcome distinct from, but associated with, health literacy. Potential useful methods, such as social network analyses, were missing from the literature. Discussion: Existing quantitative research on health literacy in a social context supports more attention to this topic. This review quantified evidence, revealed gaps, noted limitations, and identified important questions for future research.